p38 MAPK Is a Major Regulator of Amyloid Beta-Induced IL-6 Expression in Human Microglia - Lin, Houmin; Dixon, Steven Grant; Hu, Wei; Hamlett, Eric D.; Jin, Junfei; Ergul, Adviye; Wang, Gavin Y. (Molecular neurobiology, 2022)
The accumulation of amyloid beta (Aβ) plaques in the brain is a hallmark of Alzheimer’s disease (AD) pathology. Microglial activation-mediated neuroinflammation has been implicated in the pathogenesis of AD and the expression levels of interleukin-6 (IL-6) were increased in the brains of AD patients. However, the mechanisms by which IL-6 expression is regulated in human microglia are incompletely understood. Here, we show that Aβ 1-40 oligomers (Aβ 40 ) dose-dependently stimulate IL-6 expression in HMC3 human microglial cells. Treatment with Aβ 40 promotes the transcription of IL-6 and tumor necrosis factor α (TNFα) mRNAs in both HMC3 and THP-1 cells. Mechanistic studies reveal that Aβ 40 -induced increase of IL-6 secretion is associated with the activation of p38 mitogen-activated protein kinase (p38 MAPK). Inhibition of p38 MAPK by BIRB 796 or SB202190 abrogates Aβ 40 -induced increase of IL-6 production. Through analyzing brain specimens, we found that the immunoreactivity for IL-6 and phosphorylated (the activated form) p38 MAPK was markedly higher in microglia of AD patients than in age-matched control subjects. Moreover, our studies identified the co-localization of IL-6 with phosphorylated p38 MAPK in microglia in the cortices of AD patients. Taken together, these results indicate that p38 MAPK is a major regulator of Aβ-induced IL-6 production in human microglia, which suggests that targeting p38 MAPK may represent a new approach to ameliorate Aβ accumulation-induced neuroinflammation in AD.